ANALISIS POTENSI SEKTOR PARIWISATA DALAM PENINGKATAN PENDAPATAN DAERAH KOTA PALANGKA RAYA - Leo Arya Pamungkas; Nita Beti Lestari, Jeremi Aexona Silallahi, Rahmah Norhayati, Agustina Siagian, Suherman (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to explore the correlation between the tourism sector and regional income in the city of Palangkaraya. Data collection was carried out through a quantitative approach using data from the Central Statistics Agency (BPS), Ministry of Finance, sources such as e-books, and so on. The way to analyze it is to look at trends and carry out multiple linear regression calculations. The findings from the study show that, from 2018 to 2022, the potential of the tourism sector will fluctuate in influencing regional income in the city of Palangkaraya. This research found that the number of tourists and tourist attractions does not have a big impact on regional income, but the existence of travel agencies turns out to have quite a big influence on the regional income of the city of Palangkaraya.